2020
DOI: 10.1016/j.cmi.2020.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictors of death among 4035 consecutively hospitalized patients with COVID-19 in Spain

Abstract: Objectives To analyse the characteristics and predictors of death in hospitalized patients with coronavirus disease 2019 (COVID-19) in Spain. Methods A retrospective observational study was performed of the first consecutive patients hospitalized with COVID-19 confirmed by real-time PCR assay in 127 Spanish centres until 17 March 2020. The follow-up censoring date was 17 April 2020. We collected demographic, clinical, laboratory, treatment and complications data. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
250
14
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(355 citation statements)
references
References 29 publications
55
250
14
18
Order By: Relevance
“…Epidemiological data reveals that individuals over 60 years of age are disproportionately affected by SARS-CoV-2 infection experiencing the most severe forms of disease and the highest hospitalization rates (178)(179)(180). Age is a strong predictor of death among patients hospitalized with COVID-19 (181,182) and a review of epidemiological data from different countries revealed an exponential increase in case fatality rates with age, regardless of the geographic region (183). Despite being the most affected risk group, older adults are the least likely to respond to a new vaccine.…”
Section: Reflections On Covid-19 Vaccination Strategies For the Elderlymentioning
confidence: 99%
“…Epidemiological data reveals that individuals over 60 years of age are disproportionately affected by SARS-CoV-2 infection experiencing the most severe forms of disease and the highest hospitalization rates (178)(179)(180). Age is a strong predictor of death among patients hospitalized with COVID-19 (181,182) and a review of epidemiological data from different countries revealed an exponential increase in case fatality rates with age, regardless of the geographic region (183). Despite being the most affected risk group, older adults are the least likely to respond to a new vaccine.…”
Section: Reflections On Covid-19 Vaccination Strategies For the Elderlymentioning
confidence: 99%
“…An interesting finding in this study was there were not remarkable alterations in laboratory counts among all patients. Leukopenia and thrombocytopenia were the most common alterations reported in many other series 9,11,12 , and regarding inflammatory markers, elevations in CRP, ferritin a DD, have been associated with severe COVID and a higher risk of ventilation or ICU admission. Indeed, we found those who were admitted to ICU, tended to have higher ferritin and CRP (median 508 and 7.2, respectively) than those who did not require ICU (median 358 and 3.5, respectively), but the values were not as high as other reports.…”
Section: Discussionmentioning
confidence: 78%
“…Based on clinical and epidemiological analyses, older age, male and preexisting comorbidity were identi ed as important risk factors for the development of severe or lethal disease in COVID-19, which were similar to SARS and MERS [22][23][24]. The ve most common comorbidities were hypertension, diabetes, cardiovascular disease, chronic obstructive pulmonary disease and tumor, while higher D-dimer, higher neutrophil/lymphocyte ratio, higher level of Creactive protein, lymphopenia, thrombocytopenia and obesity were the independent risk factors of death in COVID-19 patients [25][26][27]. According to epidemiology and large scale data, diabetes has been identi ed as an important risk factor for mortality and rates of progression to acute respiratory distress syndrome (ARDS) in hospitalized patients with COVID-19 [28,29].…”
Section: Discussionmentioning
confidence: 99%